The martyrs' cry - Voice of the Martyrs (Organization); Goad Family (Musical group) (Bartlesville, Okla. : Stephen Yake Productions, 1952)
David Goodnow interviews Christians in different parts of the world that have been persecuted for their faith in Jesus Christ.
Sudan - the scars of faith -- Southeast Asia - revival in the mountains -- Indonesia - the plans I have for you.
Hosted by CNN's David Goodnow.
"Give it all to Jesus" sung by the Goad Family.
VHS.
Keywords: Persecution -- Sudan; Persecution -- Indonesia; Persecution -- Southeast Asia; Persecution -- Vietnam; Christianity -- 20th century; Christianity -- Sudan; Christianity -- Indonesia; Christianity -- Southeast Asia; Christianity -- Vietnam